More tales to keep you up at night - Poblocki, Dan (Penguin Workshop, 2023)
Gilbert's visit to his injured brother takes a haunting turn when he discovers a mysterious satchel of cassette tapes containing chilling stories that seem to hold the key to saving his brother, but he may be opening a door to something much, much worse.